2018
DOI: 10.24200/jonus.vol3iss2pp32-40
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Practicum of an English Teacher Education Program in Vietnam: From Expectations to Reality

Abstract: Teaching practicum is very essential in the process of learning how to teach, so it should be paid great attention by not only teacher education program designers but also implementators. The paper reports a study on the efficiency of teaching practicum which has been conducted at Public University (pseudonym) in Vietnam. The research employed qualitative approach, and semi-structured interviews were used as the instrument for the data collection. Findings reveal that the implementation of the teaching practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
5
17
0
Order By: Relevance
“…The presented interview excerpts showed that all participants expressed positive emotion towards their participation in the school-based practicum as their first experiences joining the program. The finding echoed prior studies which reported that the PSTs showed positive emotions like feeling excited (Vo, et. al., 2018), interested and enthusiastic (Hascher, et.…”
Section: Psets' Emotion and Factors Shaping Itsupporting
confidence: 86%
See 4 more Smart Citations
“…The presented interview excerpts showed that all participants expressed positive emotion towards their participation in the school-based practicum as their first experiences joining the program. The finding echoed prior studies which reported that the PSTs showed positive emotions like feeling excited (Vo, et. al., 2018), interested and enthusiastic (Hascher, et.…”
Section: Psets' Emotion and Factors Shaping Itsupporting
confidence: 86%
“…With socialization by the university supervisor who explained the nature of the program, the PSETs understood the tasks they should accomplish which eventually eased them and shifted the negative feelings to positive ones. Prior studies emphasized that lack of guidance from mentor teachers and university supervisors makes practicum less effective (Vo, et. al., 2018) and reduce the quality of the practicum program (Sulistyo, et.…”
Section: Psets' Emotion and Factors Shaping Itmentioning
confidence: 99%
See 3 more Smart Citations